Silicon fluxes and isotope composition of direct groundwater discharge into the Bay of Bengal and the effect on the global ocean silicon isotope budget - Georg, R; West, A; Basu, A; Halliday, A (2009)
This study presents silicon isotope data for rivers and groundwater from the Bengal Basin. Variations of Si isotope ratios were analyzed by means of high-resolution MC-ICP-MS using a NuPlasma HR. The rivers show typical positive δ30Si values between 1.3 and 1.7‰, whereas the groundwater samples show decreasing δ30Si values from 1.3‰ in shallow groundwater to - 0.2‰ in the deeper groundwater. Beside a very distinctive isotope composition, the concentration of dissolved Si in these groundwater samples is 2-3 times higher than in river samples taken during dry season. The resulting Si flux by groundwater (9.3 × 1010 mol yr- 1) is on the order of the combined Ganges-Brahmaputra Si fluxes, and equals 40% of the total (river + groundwater) annual Si flux into the Bay of Bengal. Given the significant large flux and distinctive isotope composition means that the overall isotopic input into the ocean is different from riverine values. However, a sound knowledge of all inputs into the ocean and of how these inputs might vary throughout time is mandatory, in order to correctly interpret palaeo-records of δ30Si variations as recorded in sedimentary diatom opal from the last glacial maximum. We extrapolate our results from the Bengal Basin onto a global scale and assess the ocean's sensitivity to changes in inputs, as triggered by large-scale events, such as glaciation periods, where the hydrological cycle might be out of steady state due to the build-up of large continental ice-shields. In such a glaciation scenario, riverine vs. groundwater inputs can be shifted, favoring isotopically lighter groundwater over heavier river inputs into the ocean. The model proves impossible to change the biogenic output to a significant degree, on time scales of a few thousand years, by just changing the isotope inputs into the ocean. © 2009 Elsevier B.V. All rights reserved.